Le camp F de Lautagne à Valence (Drôme) : l’organisation interne et la vie quotidienne d’un camp militaire romain au milieu du ier s. av. J.-C. - Magalie Kielb Zaaraoui; Loïc Buffat; Michel Reddé; Yahya Zaaraoui (Gallia)
The triangular plateau of Lautagne overlooks the landscape south of Valence, and the Rhône, located a few hundred metres to the west. Combining a flat expanse of land, wide and steep slopes to the north and west, the area represents an ideal location for military settlement and surveillance; the plateau is easily defended, and faces the first foothills of the Massif Central. The site has been the subject of numerous surveys and test trenches since the early 1990s, which led to the discovery of no fewer than six defensive systems toward the end of the 2nd and 1st c. BC. Between the end of 2013 and the end of 2016, two extensive excavations were carried out on an area measuring just over 13.7 ha. They explored the south-eastern corner of Camp F, the subject of this article. Little material allowing for dating was found therein; neither ceramic nor numismatic goods were retrieved. Current consensus attributes the camp’s dating range to the second quarter of the 1st c. BC. The enclosure ditch has been precisely identified over nearly 660 m on its southern side and 460 m on its eastern side. It forms a particularly imposing defensive perimeter, with an opening width of 5 m, a depth of 3 m, and a V-shaped profile. The study of the ditch backfill is rich in information thanks to the cross-referencing of archaeological and geoarchaeological data. It demonstrates a repetitive filling pattern, composed of voluminous sediment layers, containing gravel from inside the camp, and loess from outside the camp. It is obvious that the Roman army performed a rigorous sorting of materials, laid out on one side or the other of the ditch, according to need. Though the enclosing rampart has entirely disappeared, we know that it was composed of upcast material from the ditch. Loess layers formed an advanced defensive obstacle outside the camp. Gravel layers constituted an earthen embankment (measuring, on average, more than 6 m wide) between the edge of the ditch and the first internal components of the camp. The presence of quadrangular earthen blocks in the ditch backfill suggests that a mud-brick facing provided vertical stability to the agger. While the width of its base is approximately known, its height remains difficult to estimate. No layers of colluvial or aeolian origin are attested to in the ditch stratigraphy. This indicates with certainty that the ditch remained open for a relatively short period of time, a few weeks or months at most. Two entrances to the camp were observed on the eastern and southern border. These access points assume the form of an external clavicula, measuring about 12 m in diameter and right-angled, as opposed to being semi-circular in shape, which represents an archaeological novelty. A series of twelve pits dug within the eastern feature was also uncovered, forming a perfect square measuring 9 m on each side. The deepest pits reach the gravel terrace, likely serving to securely seat wooden posts. These would logically have been used to support a substantial wooden structure, likely a gate-tower, such as the one reconstructed at Lunt’s Roman fort in Baginton (England). In the end, total dimensions for the camp are not known, as no ditch was identified to the north, during the surveys, that would have served to close off the camp. Nonetheless, it is assumed that the site must have occupied between 38 and 46 ha, and that between 10,000 and 15,000 (?) men, depending on the size of the auxiliary forces, could have been stationed at Lautagne for a summer campaign. Within the camp, 290 structures were preserved over some 9 ha, 119 of which have been identified as cooking ovens, sometimes accompanied by evacuation or ash pits. These structures, which underwent some form of refurbishment, invariably possess identical morphologies. They are composed of an oval-shaped, rubble earthen heating area, mostly measuring between 1 m and 1.30 m in diameter, and which opens onto a working pit. There are also two dryers/smokehouses and ovens opening onto the enclosure ditch, which was half-filled at the time of use. The different fill levels of these structures are very often identical: a dumping level of broken amphorae and/or pebbles on the surface and more or less carbonaceous levels underneath. Moreover, these are the only contexts containing archaeological material, few remains have been collected from the enclosure ditch. The material consists of ceramic goods (amphora, common ceramics, fine ceramics and unturned ceramics), pebbles, charcoal, seeds and fragmentary metal objects. A large amount of information has been gathered about the daily life and diet of Roman soldiers in the mid-1st c. BC, particularly concerning cereal consumption. At Lautagne, barley was the most commonly consumed grain on site (60%, compared to 23% wheat), leading us to assume that during the middle of the 1st c. BC, the legionnaire’s diet probably included a large ration of barley, as opposed to wheat. Finally, in the well-preserved areas, archaeological remains are distributed within groups of structures and organised in large alignments, parallel or perpendicular to the fortification axis. We suggest that this organisation is related to the camp’s internal pathways, the intervallum, as well as the areas dedicated to use for Roman soldiers’ tent installations. Because of the large number of uncertainties at the outset, it seems risky to theoretically reconstruct the camp. However, after examining various archaeological and textual sources in ideally preserved areas and according to the measurements provided by Ps.-Hygin, we have nonetheless attempted to re-imagine how the soldiers would have set up their tents at Lautagne F.